Clinical efficacy and safety of modified Sijunzi decoction for the treatment of ulcerative colitis: A protocol for a systematic review and meta-analysis. Issue 4 (29th January 2021) - Tian, Shu Wei; Zhang, Yan Ling; Wang, Bin; Liu, Ji Ping; Wang, Chuan; Zhang, Juan
Abstract: Background: Ulcerative colitis (UC) is a chronic non-specific intestinal inflammatory disease with unknown etiology. In recent years, the global incidence has been increasing. Sijunzi decoction (SJZD) is a traditional Chinese medicine that has been used for treatment of other diseases in previous studies as it has no side effects and it has a pharmacological effect in gastrointestinal function, immune system, ulcers, and tissue repair. Methods: PubMed, Embase, Cochrane Library, GeenMedical, China National Knowledge Infrastructure, Chinese Sci-tech Journals full-text Database, Chinese Biomedical Database, and Chinese Science Citation Database were searched to screen the related literatures of "ulcerative colitis" and "Jiawei Sijunzi decoction". The research data extracted from above studies was analyzed by Review Manager 5.3 and Stata14.2 software. Results: This systematic review and meta-analysis will evaluate the efficacy and safety of Jiawei SJZD in the treatment of UC and provide effective evidence for clinical use. Conclusion: In this study, the published evidence of modified SJZD in the treatment of UC was systematically summarized and evaluated, so that it can be better applied in clinic. INPLASY registration number: INPLASY2020100102